Sonic Hedgehog Regulates Proliferation, Migration and Invasion of Synoviocytes in Rheumatoid Arthritis via JNK Signaling - Zhu, Shangling; Ye, Yuanmei; Shi, Yiming; Dang, Junlong; Feng, Xiaoxue; Chen, Yingdi; Liu, Fang; Olsen, Nancy; Huang, Jianlin; Zheng, Song Guo (Frontiers in Immunology, 2020)
Activated fibroblast-like synoviocytes (FLSs) play a central role in the formation of synovial pannus and joint destruction in rheumatoid arthritis (RA). Targeting FLSs could be a potential therapeutic strategy. The objective of this study is to explore the role of c-Jun N-terminal kinase (JNK) in proliferation, migration and invasion of FLSs promoted by the sonic hedeghog (SHH) signaling pathway in patients with RA. Activation of SHH signaling was evaluated by real-time PCR and Western Blot. Levels of phosphorylation of JNK and c-Jun were detected by Western Blot. FLSs proliferation was quantified by Cell Counting Kit-8 (CCK-8) assay and flow cytometry. Cell migration and invasion were assessed by wound healing assay and Transwell chamber assay. Invasiveness of FLSs in vivo was evaluated using a humanized synovitis animal model. We observed that treatment of SHH agonist (SAG) significantly increased the levels of phosphorylation of JNK and c-Jun, while SHH antagonist (cyclopamine) significantly decreased the expression of phospho-JNK and phospho-c-Jun in FLSs. The elevated level of phospho-c-Jun stimulated by SAG was decreased in the presence of JNK inhibitor (SP600125) (P<0.001). FLSs proliferation, migration and invasion were promoted by SHH agonist (P<0.05). However, the enhanced aggressiveness of FLSs was abolished in the presence of JNK inhibitor (P<0.05). In vivo study showed that the invasion of FLSs into cartilage was increased by SHH overexpression and the excessive invasiveness was inhibited by blockade of JNK signaling (P<0.01). These results suggest that JNK is one of the downstream molecules mediating the effect of SHH signaling in FLSs. These findings indicate that SHH-JNK signaling could be a potential therapeutic target to suppress the aggressiveness of FLSs and prevent articular damage of RA.